2001
DOI: 10.1054/bjoc.2000.1691
|View full text |Cite
|
Sign up to set email alerts
|

EGCG, a major component of green tea, inhibits tumour growth by inhibiting VEGF induction in human colon carcinoma cells

Abstract: Catechins are key components of teas that have antiproliferative properties. We investigated the effects of green tea catechins on intracellular signalling and VEGF induction in vitro in serum-deprived HT29 human colon cancer cells and in vivo on the growth of HT29 cells in nude mice. In the in vitro studies, (-)-epigallocatechin gallate (EGCG), the most abundant catechin in green tea extract, inhibited Erk-1 and Erk-2 activation in a dose-dependent manner. However, other tea catechins such as (-)-epigallocate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
181
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(194 citation statements)
references
References 28 publications
11
181
0
Order By: Relevance
“…New data (Cao et al, 1999) indicate that EGCG suppresses endothelial cell growth in vitro and the formation of new blood vessels in chick chorioallantoic membrane; drinking green tea significantly prevents corneal vascularisation induced by one of the most potent angiogenetic factors (VEGF). The same results have been obtained by Jung et al (2001) in in vitro studies, in serum-deprived HT29 cells, and in in vivo studies, on the growth of HT29 cells in nude mice. EGCG exerts, at least part of its anticancer effect, by inhibiting angiogenesis through blocking the induction of VEGF in both in vitro and in vivo studies, while EGC, ECG and EC have not demonstrated the same effect (Jung et al, 2001).…”
supporting
confidence: 82%
“…New data (Cao et al, 1999) indicate that EGCG suppresses endothelial cell growth in vitro and the formation of new blood vessels in chick chorioallantoic membrane; drinking green tea significantly prevents corneal vascularisation induced by one of the most potent angiogenetic factors (VEGF). The same results have been obtained by Jung et al (2001) in in vitro studies, in serum-deprived HT29 cells, and in in vivo studies, on the growth of HT29 cells in nude mice. EGCG exerts, at least part of its anticancer effect, by inhibiting angiogenesis through blocking the induction of VEGF in both in vitro and in vivo studies, while EGC, ECG and EC have not demonstrated the same effect (Jung et al, 2001).…”
supporting
confidence: 82%
“…16,33 As noted earlier, EGCG is present in feces but undetectable in urine. Thus, our observed EGC-colon cancer association may reflect, at least in part, a major direct role of EGCG in colon cancer protection in humans.…”
Section: Discussionmentioning
confidence: 72%
“…Recent studies have established that 2 can act as a potential anti-angiogenic compound. [27][28][29][30][31][32] In the present study, 2 (100 μM) moderately activated HIF-1 under normoxic conditions and did not inhibit hypoxia-induced HIF-1 activation. Chemical stability studies suggest that the lack of stability of 2 in this cell-based in vitro system may contribute to its relatively weak HIF-1 regulatory activity.…”
mentioning
confidence: 76%